2015
DOI: 10.4238/2015.june.29.2
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant of the β-lactamase ADC-61 gene in multi-drug resistant Acinetobacter baumannii

Abstract: ABSTRACT. The aim of this study was to investigate the existence of a β-lactamase gene in a group of multi-drug resistant Acinetobacter baumannii. Twenty strains of multi-drug resistant A. baumannii were isolated. Thirty-four β-lactamase genes and the ISaba1-OXA-23 linkage were analyzed in these strains by polymerase chain reaction (PCR) and verified by DNA sequencing. Three kinds of β-lactamase genes (TEM, ADC, and OXA-23) were identified, among which the sequence of strain No. 20, ADC, was different from ADC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…TEM-1 encodes a class A β-lactamase, and has been found in many CR A. baumannii strains in different regions. [ 18 21 ] It also contributed to CR occurrence in our study, as all the CR isolates carrying this gene showed positive expression.…”
Section: Discussionmentioning
confidence: 53%
“…TEM-1 encodes a class A β-lactamase, and has been found in many CR A. baumannii strains in different regions. [ 18 21 ] It also contributed to CR occurrence in our study, as all the CR isolates carrying this gene showed positive expression.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, bla TEM– 1 and in a smaller proportion bla CTXM– 1 which belong to β-lactamases of class A, were also detected. The presence of these β-lactamases has been previously associated with the resistance to the third and fourth generation of cephalosporins and carbapenems and they are also associated with other β-lactamases from other families causing multi-drug resistance phenomena (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The rise in nosocomial MDR ABC infections has been a serious concern worldwide with the increasingly widespread use of broad-spectrum antibiotics. Although many studies across the world on nosocomial MDR ABC have been reported, they were mostly focused on adults [2123]. This study was executed because the data focusing on children with nosocomial MDR ABC were lacking.…”
Section: Discussionmentioning
confidence: 99%